Implications of Helicobacter pylori infection for stomach cancer prevention - Karen J. Goodman
Accumulating evidence has implicated Helicobacter pylori, an established cause of chronic gastritis and peptic ulcer, in the etiology of gastric cancer. Control of this infection would reduce the occurrence of chronic gastritis and peptic ulcer and might substantially lower the risk of stomach cancer as well. The public health impact of this infectious agent warrants efforts to identify preventive measures. This paper reviews the evidence linking H. pylori infection to gastric cancer and evaluates the potential for control in high-risk populations. Current obstacles to H. pylori control are discussed, including the link to poor socioeconomic conditions, difficulty in identifying incident cases, lack of natural immunity to reinfection, limited effectiveness of antibiotic therapy in high-prevalence populations, and incomplete knowledge regarding the reservoir of infection, mode of transmission, host susceptibility factors, and the potential for developing an effective vaccine. Worthwhile avenues of research include studies designed to identify modifiable risk factors for acquisition of the infection, modifiable host factors that may increase resistance to chronic infection, more effective antibiotic therapies, and effective vaccines.